DESIGN PARA O COMPORTAMENTO SUSTENTÁVEL: REVISÃO DE ESTUDOS EMPÍRICOS - Franceschini, Paula; Rocha, Cecilia da (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Design for Sustainable Behaviour is an approach that focus on influence users to behave more sustainably through the product design. Some empirical studies based on this approach have been developed during the last fifteen years. This paper aims to analyse these studies found in literature in order to identify the design processes and the design strategies most utilized and their contributions to the built environment. First, a systematic review has been realized. Then, the 67 studies selected have been compared considering the year of publication, the focus of the study and its method. The number of empirical studies of Design for Sustainable Behaviour have increased during the last decade, showing that it is still a relevant field. Yet, the majority of the studies are in the residential context and with the focus in adults activities and energy consumption. The main design strategy utilized is the feedback and its effectiveness have already been proved in many studies. The results of this literature review present the lack in knowledge to be filled by future research.